2021
DOI: 10.3390/d13030133
|View full text |Cite
|
Sign up to set email alerts
|

Animal Forest Mortality: Following the Consequences of a Gorgonian Coral Loss on a Mediterranean Coralligenous Assemblage

Abstract: In this work, the consequences of a local gorgonian coral mortality on the whole coralligenous assemblage were studied. A Before/After-Control/Impact sampling design was used: the structure of the coralligenous assemblage was compared before and after the gorgonian mortality event at the mortality site and two control sites. At the mortality site, a relevant decrease in alpha and beta diversity occurred, with a shift from a stratified assemblage characterized by gorgonians and other invertebrates to an assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…Sessile organisms are particularly vulnerable to hypoxic events because they cannot move or migrate to well‐oxygenated water. Furthermore, sessile organisms include many important habitat‐forming species, so any change in their abundance could have major consequences for the ecosystems they support (Piazzi et al, 2021; Vergés et al, 2019; Woodhead et al, 2019). Therefore, it is critical to understand how these organisms respond to hypoxia to predict possible future changes and effectively manage marine ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Sessile organisms are particularly vulnerable to hypoxic events because they cannot move or migrate to well‐oxygenated water. Furthermore, sessile organisms include many important habitat‐forming species, so any change in their abundance could have major consequences for the ecosystems they support (Piazzi et al, 2021; Vergés et al, 2019; Woodhead et al, 2019). Therefore, it is critical to understand how these organisms respond to hypoxia to predict possible future changes and effectively manage marine ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…According to CARLIT, more than 50% of the rocky coastline of the Capo Carbonara AMP is characterized by species with a medium to medium-high level of sensitivity (Ballesteros et al, 2007;Atzori et al, 2020), thus indicating good water quality. Similarly, the ESCA index, which is known to be sensitive to human disturbances (Piazzi et al, 2021b), displayed high values. These outcomes underline how proper management can positively affect both shallow macroalgal communities and circalittoral coralligenous assemblages.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the diversity of the intermediate layer and the conditions of the upper layer seem to be sentinels of climate change (Piazzi et al, 2017b). Recent comparative studies reported significant changes in the deep reef communities of Capo Carbonara MPA over the last 20 years (Azzola et al, 2022), including a local mass mortality event of gorgonians following summer heatwaves (Piazzi et al, 2021b). Boundaries of MPAs do not constitute a physical barrier against sea warming.…”
Section: Discussionmentioning
confidence: 99%
“…We also use long‐term averages to represent dynamic variables (1995–2014 and 2080–2099 for present and future conditions, respectively) so that any temporary climate events affecting coral survival are not considered. Although mass mortality events from marine heat waves are mostly reported from shallow waters (e.g., Piazzi et al, 2021 ), marine heat waves can also affect the deep‐sea (Elzahaby & Schaeffer, 2019 ), with potential for increased mortality for deep‐sea corals and associated taxa if sufficiently severe.…”
Section: Discussionmentioning
confidence: 99%